A Comparative Study Between Teenagers and Adult Mothers’ Knowledge Towered Breast Feeding of Infants at Baghdad Teaching Hospitals - Jaddoue, Ilham Amin; Qasim, Anwar Saad; Marbut, Mousa Mahmoud (Medical Science Journal for Advance Research, 2025)
Background: The ideal approach for a mother’s health and a baby’s healthy development and growth is breastfeeding. According to the World Health Organization, infants should only be breastfed in the initial half-year of life. The literature has extensively documented the advantages of nursing for both mothers and their offspring. Breastfeeding causes the mother to release the chemicals oxytocin and prolactin, which encourage intimacy and tenderness with the child. Objective: to identify the effect of Age Variable of Mothers towered Breastfeeding of Infant. Methods and Materials: An assessment of young mothers’ knowledge regarding nursing was done by a descriptive research on the topic between November 1, 2024, until September 1, 2025. The Pediatric Teaching Hospital and Medical City/Baghdad Teaching Hospital served as the study’s sites. 100 moms from Medical City/Baghdad Teaching Hospital and Pediatric Teaching Hospital were included in the purposive sample. The mother was chosen during the same time frame as the data collecting. The Statistical Program for Social Sciences ( SPSS ) version 26.0 was used to evaluate the data, with an emphasis on standard deviation, mean score, frequency, and percentage. The associations between mothers’ demographic traits—such as their age, schooling, and occupation—and their knowledge were ascertained using the chi-square test. Based on the mean score, the knowledge was divided into three levels: 1.68-2 = High, 1.34-1.67 = Moderate, and 1.1-33 = Low. Findings: Adult mothers ranged in age from 32.24 to 9.120 years, with 86% of them being housewives and 32% having college degrees. Teenage mothers were 17.48±1.474 years old, all of them owned a home, and 26% of them couldn’t read or write. The respondents’ ages were 35.28±3.078 during their first pregnancy, 20.24±5.081 during their marriage, and 21.44±5.269 during their first pregnancy. In contrast to the survey’s sample of adult mothers, 46% of the respondents used a combination of foods during the previous feeding, 52% had a pregnancy lasting one to three months, and 62% possessed a delivery lasting one to three months. Young mothers reported that 40 percent of them had previously used advertisement feeding, and 98 percent had a pregnancy lasting one to three months, a birth lasting one to three months, and an age of 17.23±4.251 during the pregnancy, 14.940±1.391 during the wedding celebration, and 15.62±1.105 through the first delivery. Conclusion: The vast majority of the moms in this study are well-versed in breastfeeding. The understanding of older mothers regarding breastfeeding was higher than that of teenage mothers.